2001
DOI: 10.1002/jbm.1258
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and release properties of growth factors from biodegradable implants

Abstract: The present investigation was performed to study the adsorption behavior of growth factors and their release characteristics from biodegradable implants in an in vitro study. We investigated the stability of growth factors administered on various scaffolds. We used porous tricalcium phosphate ceramics (alpha-TCP), a neutralized glass-ceramics (GB9N), a composite (polylactid/-glycolid/GB9N), and solvent dehydrated human bone as carriers. Block shaped scaffolds (sized: 7 x 7 x 10 mm) were loaded with 5 microg of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 19 publications
6
83
0
Order By: Relevance
“…A much faster release was observed for scaffold incorporated with PLGA50-6.5K microspheres than that with PLGA50-64K microspheres. Microsphere incorporation also protects bioactive growth factors from denaturing as compared to direct adsorption of growth factors onto the biodegradable scaffolds/implants, which results in complete degradation of growth factors such as rhVEGF, BMP-4 and bFGF during a very short release time of 3days [40]. Our in vitro bioactivity assay indicated that no significant bioactivity loss was found for PDGF-BB during encapsulation into PLGA microspheres using double emulsion technique and upon initial in vitro release in PBS.…”
Section: Discussionmentioning
confidence: 75%
“…A much faster release was observed for scaffold incorporated with PLGA50-6.5K microspheres than that with PLGA50-64K microspheres. Microsphere incorporation also protects bioactive growth factors from denaturing as compared to direct adsorption of growth factors onto the biodegradable scaffolds/implants, which results in complete degradation of growth factors such as rhVEGF, BMP-4 and bFGF during a very short release time of 3days [40]. Our in vitro bioactivity assay indicated that no significant bioactivity loss was found for PDGF-BB during encapsulation into PLGA microspheres using double emulsion technique and upon initial in vitro release in PBS.…”
Section: Discussionmentioning
confidence: 75%
“…64,65 Ideally, the sustained release from the scaffolds would provide more persistent stimuli over time to aid the differentiation of bone marrow stromal cells or other progenitor cells that would be found at a cartilage defect site. 54 Although the IGF-1 release profile from the collagen-GAG scaffold was slightly lower than 50 ng IGF-1/mL/day over 14 days for all loading groups, previous work has suggested that concentrations of IGF-1 as low as 10 ng/mL are sufficient to stimulate the metabolic actions of cultured chondrocytes. 34 There are reports of in vivo osteochondral repair being enhanced by IGF-1 after 8-12 weeks.…”
Section: Igf-1 Dosagementioning
confidence: 77%
“…The majority of IGF-1 release (26%-44% of the loaded IGF-1) occurred in a rapid burst release up to 24 h. This was followed by a slow controlled release in which a further 13%-16% was released between days 1 and 14. Many studies have reported similar burst releases of growth factor from such delivery devices occurring within the first 24 h. 45,[51][52][53][54] For example, Ueda et al reported that *30% of transforming growth factor-b1 incorporated in a collagen scaffold was released into the PBS by simple diffusion within the first hour of an in vitro release test. 53 We found that the percent of IGF-1 released after 24 h depended on the initial IGF-1 loading concentration and that therefore reducing the volume or loading concentration of IGF-1 could be used to reduce the burst release from this system.…”
Section: Elution Of Igf-1mentioning
confidence: 98%
“…Incorporation of angiogenic growth factors such as basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF), among others, into scaffolds for controlled release has been shown to promote local angiogenesis. [10,13] There are many methods to incorporate growth factors into synthetic scaffolds, such as absorbing growth factor to the scaffold, [14] blending growth factor containing microspheres into the scaffold, [10,15] or directly mixing growth factor containing protein powder into the scaffold during processing. [16,17] Adsorbing growth factor onto the scaffold has the drawback of low loading efficiencies and rapid release.…”
Section: Introductionmentioning
confidence: 99%